Long Term Follow-up after Endoscopic Endonasal Approach for the Treatment of Cushing's Disease - Todeschini, Alexandre Bossi (J Neurol Surg B Skull Base, 2019)
Introduction  Surgery has been the standard treatment for Cushing's disease. Currently, the endoscopic endonasal approach (EEA) is the most widely used technique. However, among some endocrinologists and neurosurgeons used to the microscope assisted technique, there are still questions about the effectiveness and safety of transitioning to the EEA. We aim to show our initial experience with such transition. Method  Retrospective review of medical records of patients, who underwent EEA in our center as a first treatment for Cushing's disease, and with a minimum 18 months of follow-up, from March 2004 to March 2014 Results  Our cohort had 16 patients (14 females and 2 males), with a mean age of 33.7 years. The mean follow-up was 52.0 months. Magnetic resonance imaging (MRI) identified an adenoma in 93.8% of the patients (56.2% microadenomas and 37.5% macroadenomas). Postoperative cerebrospinal fluid (CSF) leak was observed in two patients (12.5%). No new neurological deficits were present after surgery. The early remission and sustained remission rates after a single procedure were 87.5 and 68.75%, respectively. Weight reduction, improved control of blood pressure, and lower serum glucose levels were documented in 68.75, 60, and 55.5% of patients, respectively, after remission. Conclusion  Despite the need for specialized training, equipment and team building by ENT (Ear, Nose and Throat) and neurosurgery, the transition from microscope assisted pituitary surgery to endoscopic endonasal approach is possible and safe. The clinical outcomes, even in the early years, are similar to the previous microscope assisted treatment, and over time, with greater experience and knowledge, there is a tendency for improvement.